2009
DOI: 10.1111/j.1440-169x.2009.01103.x
|View full text |Cite
|
Sign up to set email alerts
|

Cnidarians and the evolutionary origin of the nervous system

Abstract: Cnidarians are widely regarded as one of the first organisms in animal evolution possessing a nervous system. Conventional histological and electrophysiological studies have revealed a considerable degree of complexity of the cnidarian nervous system. Thanks to expressed sequence tags and genome projects and the availability of functional assay systems in cnidarians, this simple nervous system is now genetically accessible and becomes particularly valuable for understanding the origin and evolution of the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
179
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(184 citation statements)
references
References 189 publications
(349 reference statements)
4
179
0
1
Order By: Relevance
“…Among these, the neuropeptide RFamide family of GPCRs is the most studied among the cnidarians. RFamide-positive neurons were found in N. vectensis, Hydra, Hydractinia and jellyfish, and they are found in all classes of cnidarians (Watanabe et al, 2009 (Churcher and Taylor, 2011;Marlow et al, 2009;Nakanishi et al, 2012;Niimura, 2009). These findings provide insights that the prebilaterians exhibit a GPCR-mediated sensory system and suggested that the genetic complexity commonly assumed to have arisen much later in animal evolution is actually an ancestral feature.…”
Section: N V E C T E N S I S T a D H A E R E N S A Q U E E N S mentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, the neuropeptide RFamide family of GPCRs is the most studied among the cnidarians. RFamide-positive neurons were found in N. vectensis, Hydra, Hydractinia and jellyfish, and they are found in all classes of cnidarians (Watanabe et al, 2009 (Churcher and Taylor, 2011;Marlow et al, 2009;Nakanishi et al, 2012;Niimura, 2009). These findings provide insights that the prebilaterians exhibit a GPCR-mediated sensory system and suggested that the genetic complexity commonly assumed to have arisen much later in animal evolution is actually an ancestral feature.…”
Section: N V E C T E N S I S T a D H A E R E N S A Q U E E N S mentioning
confidence: 99%
“…dopamine and serotonin transmitters, as well as neuropeptides, are involved in cnidarian neurotransmission (Kass-Simon and Pierobon, 2007;Watanabe et al, 2009) (Fig. 2).…”
Section: N V E C T E N S I S T a D H A E R E N S A Q U E E N S mentioning
confidence: 99%
“…Individual neurons in cnidarians are highly specialized. In comparison to neurons of bilateral animals, they contain close to a complete set of signaling molecules that are involved in nervous system development, maintenance and communication (see Watanabe et al, 2009). This puts the individual neurons of cnidarians on a level of complexity similar to that of neurons of higher animals.…”
Section: Are Cnidarian Nervous Systems Made Up Of Nerve Nets?mentioning
confidence: 99%
“…1B; reviewed by Galliot et al (2009)]. Although their neurons are not uniformly distributed, cnidarian polyps lack brain-like nervous system centralization and their nervous system is often described as a nerve net (Galliot et al, 2009;Watanabe et al, 2009). The cellular origin of neurons has mainly been described in hydrozoans (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…ectoderm and endoderm (Nakanishi et al, 2012). At the molecular level, Nematostella possesses many genes related to conserved bilaterian neural genes (Putnam et al, 2007;Watanabe et al, 2009), and subsets of its nervous system have been examined using antibodies against conserved neuropeptide precursor molecules [e.g. Marlow et al (2009)].…”
Section: Introductionmentioning
confidence: 99%